1996
DOI: 10.1111/j.2042-7158.1996.tb03988.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Xanthones from Guttiferaeous Plants against Methicillin-resistant Staphylococcus aureus

Abstract: Extracts of Garcinia mangostana (Guttiferae) showing inhibitory effects against the growth of S. aureus NIHJ 209p were fractionated according to guidance obtained from bioassay and some of the components with activity against methicillin-resistant Staphylococcus aureus (MRSA) were characterized. One active isolate, alpha-mangostin, a xanthone derivative, had a minimum inhibitory concentration (MIC) of 1.57-12.5 micrograms mL-1. Other related xanthones were also examined to determine their anti-MRSA activity. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(108 citation statements)
references
References 8 publications
3
103
0
2
Order By: Relevance
“…Biological activity studies have shown that G. mangostana promotes antiinflammatory, anticancer, antimicrobial, and antioxidant properties (Iinuma et al, 1996;Nakatani et al, 2002;Moongkarndi et al, 2004;Chomnawang et al, 2005). Mangosteen fruit extract is popularly used as a food supplement due to its antioxidant activity, while the extract from the fruit rind, promoting antibacterial properties, has been recommended for the treatment of acne vulgaris (Kumar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Biological activity studies have shown that G. mangostana promotes antiinflammatory, anticancer, antimicrobial, and antioxidant properties (Iinuma et al, 1996;Nakatani et al, 2002;Moongkarndi et al, 2004;Chomnawang et al, 2005). Mangosteen fruit extract is popularly used as a food supplement due to its antioxidant activity, while the extract from the fruit rind, promoting antibacterial properties, has been recommended for the treatment of acne vulgaris (Kumar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…18) The crude extract of the hull reportedly possesses several pharmacological activities: H 1 -histamine receptor antagonistic activity, 19) anti-serotonin activity, 20) inhibition of eukaryote protein kinases and a cyclic nucleotide-binding phosphatase, 21) inhibitory activity against HIV-1 protease, 22) inhibition of the sarcoplasmic reticulum Ca 2ϩ -pumping ATPase, 23) antibacterial activation against methicillin-resistant Staphylococcus aureus, 24) and anti-oxidant action.…”
Section: Discussionmentioning
confidence: 99%
“…This family is known to be a rich source of polycyclic polyprenylated acylphloroglucinols (PPAPs) with a large spectrum of biological activities (Cuesta-Rubio et al, 2005;Marti et al, 2009). Besides, some plants of Clusiaceae family have their pharmacological properties associated with the presence of xanthone derivatives, which has antioxidant and anticarcinogenic activities (Sundaram et al, 1983;Chen et al, 1996;Iinuma et al, 1996;Suksamrarn et al, 2003;Ee et al, 2008;Chomnawang et al, 2009;Hung et al, 2009).…”
Section: Platonia Insignismentioning
confidence: 99%
“…Among the Clusiaceae family, Platonia insignis Mart., commonly known as "bacuri," is a timber and fruit native species of the Brazilian Amazon (Sundaram et al, 1983;Chen et al, 1996;Iinuma et al, 1996;Suksamrarn et al, 2003;Ee et al, 2008;Chomnawang et al, 2009;Hung et al, 2009). The bacuri fruit has a thick-skin, and is 7-15 cm long and 5-15 cm in diameter, weighing 200-1000 g, containing a large quantity of resins.…”
Section: Platonia Insignismentioning
confidence: 99%